Ekstrak Batang Pelawan (Tristaniopsis merguensis Griff.) sebagai Antibakteri pada Staphylococcus aureus dan Escherichia coli - Genta Febri Kusuma; Robby Gus Mahardika; Fajar Indah Puspita Sari (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
Currently, diseases caused by infection with pathogenic microorganisms are increasing, this is indicated by the increasing interest in antibacterial substances. This research was conducted on the stem of the pelawan plant (Tristaniopsis merguensis Griff.) with the aim of identifying the secondary metabolites contained in the extract of n-hexane, ethyl acetate, and methanol of the stem of pelawan which have the potential to have antibacterial activity. Determination of the profile of the compounds contained in the extract of pelawan stem using a qualitative phytochemical test. Antibacterial test using disc diffusion method. Phytochemical qualitative test showed positive results in the flavonoid and phenol groups. The results of the disc diffusion antibacterial test on the diameter of the inhibitory zone of the stem extract showed that the methanol extract of the stem against the S. aureus had the greatest inhibition against the bacteria S. aureus at a concentration of 10000 ppm with an average inhibitory power of 8.07 mm and against the bacteria E. coli at the concentration of 10000 ppm. concentration of 10000 ppm with an average inhibition of 8.19 mm.